2013
DOI: 10.1111/vco.12055
|View full text |Cite
|
Sign up to set email alerts
|

Mechlorethamine, vincristine, melphalan and prednisone (MOMP) for the treatment of relapsed lymphoma in dogs

Abstract: Eighty-eight dogs with relapsed lymphoma were treated with the MOMP (mechlorethamine, vincristine, melphalan and prednisone) protocol on a 28-day treatment cycle. The overall response rate (ORR) to the MOMP protocol was 51.1% for a median of 56 days (range 7-858 days). Twelve percent of dogs experienced a complete response for a median of 81 days (range 42-274 days) and 38.6% experienced a partial response for a median of 49 days (range 7-858 days). Dogs with T-cell lymphoma had an ORR of 55% for a median of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…Avoiding chemotherapy‐associated toxicity is another challenge in dogs with twice‐relapsed or refractory lymphoma due to a combination of limited drug choices, presence of advanced stage disease and chronic myelosuppression from previous protocols. In this study, the frequency and severity of haematologic toxicities were similar to those reported in primary rescue protocols (Van Vechten et al ; Rassnick et al ; Alvarez et al ; Saba et al ; Fahey et al ; Back et al ). Dogs that required a reduced dose intensity due to haematologic toxicity did not appear to have reduced response to the VBL protocol, as the PFS (28.5 days) and MST (33 days) were not statistically different than that of dogs that did not require reduction (29.5 days and 47.5 days respectively, P=0.171).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Avoiding chemotherapy‐associated toxicity is another challenge in dogs with twice‐relapsed or refractory lymphoma due to a combination of limited drug choices, presence of advanced stage disease and chronic myelosuppression from previous protocols. In this study, the frequency and severity of haematologic toxicities were similar to those reported in primary rescue protocols (Van Vechten et al ; Rassnick et al ; Alvarez et al ; Saba et al ; Fahey et al ; Back et al ). Dogs that required a reduced dose intensity due to haematologic toxicity did not appear to have reduced response to the VBL protocol, as the PFS (28.5 days) and MST (33 days) were not statistically different than that of dogs that did not require reduction (29.5 days and 47.5 days respectively, P=0.171).…”
Section: Discussionsupporting
confidence: 86%
“…Numerous rescue protocols for dogs with relapsed or refractory lymphoma have been reported, including MOPP (mustargen, vincristine, procarbazine and prednisone) (Rassnick et al 2002 ), DMAC (dexamethasone, melphalan, actinomycin D and cyctosine arabinoside) (Alvarez et al 2006 ), MOMP (mechlorethamine, vincristine, melphalan and prednisone) (Back et al 2015 ), LOPP (lomustine, vincristine, procarbazine and prednisone) (Fahey et al 2011 ), ADIC (doxorubicin and dacarbazine) (Van Vechten et al 1990 ), single-agent DTIC (dacarbazine) (Griessmayr et al 2009 ) and CCNU (lomustine) +/− L-asparaginase (Moore et al 1999 ;Saba et al 2009 ) among many more. Secondary response rates, defined as the percentage of dogs achieving a complete or partial remission, vary from 35 to 77%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, application of the new formula may be preferred for this dog. However, obtaining of lower doses of vincristine (0.6 mg/m [7]. When doxorubicin doses were calculated using BSA rather than body weight, drug concentrations and toxicoses were greater in smaller dogs [1] [29] carboplatin (300 mg/m 2 ) for osteosarcoma [30], dacarbazine and (200 mg/m 2 ) for canine hemangiosarcoma [31] corroborate the present calculated therapeutic values for cyclophosphamide, carboplatin and dacarbazine, respectively.…”
Section: Discussionsupporting
confidence: 65%
“…A multitude of single cytotoxic agents and combinations of agents have been investigated as rescue treatments for relapsed and refractory canine lymphoma, with response rates ranging from 0% to 87%; however, attempts to make direct comparisons of RAB to these historical studies are of minimal value given the non‐concurrent nature of serial investigations. With that being said, RAB's unique mechanism of action, substantial response rate and duration of response lends credence to its utility as a rescue agent.…”
Section: Discussionmentioning
confidence: 99%